Tomás de Aquino y la Dimensión racional - intelectiva (2021)
In Saint Thomas Aquinas's thinking, we find a series of im-portant considerations about nature and the “rational-in-tellective” dimension. It is not found by itself. It is part of a wider and more complex sensorineural system, the body and the culture itself. The cognitive dimension is related to the integral vision, the one that opens itself to the world’s entirety and takes to all “subject’s dimensions” in the order of being, doing, and working and it’s directed to all man’s development. This dimension is constituted by the sensory perception same as the intellect, where reason is one of the gravity centers of human life. Besides, knowledge knows the essence present in all material things as they are concei-ved, which takes us to universal knowledge. In this sense, the cognitive dimension for Saint Thomas is not only per-ceived but known, and, at the same time, it is formed by the reflexive dimension since the understanding reflects about itself: its acquaintance, its work, and deeds.